„Kronika wypadków miłosnych” wcale się nie zestarzała - Wysłouch, Seweryna (Polonistyka. Innowacje, 2015)
The author of this article analyzes The Chronicle of Love Affairs by Tadeusz Konwicki (1974) and shows that it can be still used at school. The main problems of this novel (youthful love, suicide, the identity of the protagonists) provide an opportunity to discuss current topics. The novel allows to expand the historical and literary knowledge of information in the field of Konwicki’s creativity, romantic tradition, literature of private homelands, as well as assimilate theoretical concepts, such as oniric poetics and film adaptation.